Hospitalizations for primary care sensitive conditions in Novo Hamburgo, Rio Grande do Sul - Arruda, Jocinei Santos de (2017)
Objectives: This study aimed to analyze trends in admissions for ambulatory care sensitive conditions (ACSC) in Novo Hamburgo, comparing it with the rest of the Rio Grande do Sul State, and relating it to the investments in health and the Family Health Strategy (FHS) coverage in the city, from 1998 to 2012. Methods: We conducted an ecological study. Data were obtained from the Unified Health System’s Hospital Database (SIH-SUS). The causes of ACSC were based on a national list published by the Ministry of Health. ACSC tendencies in Novo Hamburgo and the rest of the Rio Grande do Sul State were analyzed by means of their standardized rates, based on moving averages every three years, and Negative Binomial Regression. Correlation analysis was performed between the variables of interest. Results: Despite an increase of 329.26% in financial investments and the expansion of FHS coverage in the period, reaching 20.20% of the population, there was no decrease in ACSC rate trends in Novo Hamburgo. In the rest of Rio Grande do Sul, there was a reduction in ACSC, however, the rates were higher than in Novo Hamburgo during the same period. Conclusion: Although this study found no association between the decrease in ACSC rates and increased coverage for FHS, increase financial investment in health, financial investment in primary care and per capita spending on health, there is evidence that they are correlated. Probably the FHS coverage was not enough to impact the ACSC.